The Ya Ne Dah Ah School: Melding Traditional Teachings with Modern Curricula - Kerry R. Venegas (Harvard University John F. Kennedy School of Government, 2005)
This case study examines how Chickaloon Village, an Ahtna Athabascan Indian community near Anchorage Alaska, reclaimed control of its children's education, incorporated modern skills with traditional knowledge, and exceeded state and national standards stands as a proactive model of tribal self-determination, Native sovereignty, and community resourcefulness in creating a school of its own.